Factors Determining the Quality of Digital Logistics Services: The Role of Aggregators, 3PLS, and Technology in Customer Satisfaction at Bos Ampuh and Pos Indonesia - Arief Ilman Yusra; Agus Purnomo; Erna Mulyati (Cakrawala Repositori IMWI)
The rapid growth of e-commerce and digital transformation has increased the demand for integrated, reliable, and technology-driven logistics services. Digital logistics platforms, third-party logistics (3PL) reliability, and technological capabilities have become important factors in improving Logistics Service Quality (LSQ) and customer satisfaction. However, limited empirical studies have examined how these factors interact within digital aggregator-based logistics ecosystems, particularly in Indonesia. This study aimed to examine the effects of Digital Aggregator Integration, 3PL Service Reliability, and Technological Capability on Customer Satisfaction through Logistics Service Quality as a mediating variable in the context of Bos Ampuh and Pos Indonesia services. A quantitative approach with a causal research design was employed. Data were collected from 89 respondents consisting of Bos Ampuh users and relevant logistics stakeholders through questionnaires measured using a five-point Likert scale. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results showed that Digital Aggregator Integration significantly affected Customer Satisfaction and Logistics Service Quality. Meanwhile, 3PL Service Reliability and Technological Capability significantly improved Logistics Service Quality but did not directly influence Customer Satisfaction. Furthermore, Logistics Service Quality had a significant positive effect on Customer Satisfaction and served as a key mediating mechanism. The findings highlight that improving digital integration, service reliability, and technological capability should focus on strengthening logistics service quality to enhance customer satisfaction. This study contributes to the digital supply chain literature and provides practical implications for logistics providers in developing more effective technology-based service strategies.